Comparison of Subjective Feeling of Dizziness and Simple Taste/Olfactory Test Results in Elderly People (Over 60 Years Old) (Global Journal of Medical Research, 2022)
For a long time the author has been involved in taste and smell with Yakumo Town rural residents in Hokkaido and Nagoya-City urban in Aichi Prefecture Participants answered a self-administered questionnaire and then took a simple salty taste test and a simple olfactory test However until now the author has not been able to compare the results of a questionnaire survey of Yakumo Town Hokkaido and residents of Nagoya City Aichi Prefecture Therefore this time we will report the results 201 residents of Yakumo Town 95 men 106 women 2019 data and 55 residents of Nagoya City 24 males and 31 females 2022 data participated in the examination A self-reported questionnaire was given to the participants to determine the presence or absence of dizziness 1 no dizziness 2 dizziness and 3 dizziness all the time
Keywords: dizziness; taste; olfactory; questionnaire survey